Sub-bandgap charge harvesting and energy up-conversion in metal halide perovskites: ab initio quantum dynamics - Bipeng Wang; Weibin Chu; Yifan Wu; Wissam A. Saidi; Oleg V. Prezhdo (npj Computational Materials)
Abstract Metal halide perovskites (MHPs) exhibit unusual properties and complex dynamics. By combining ab initio time-dependent density functional theory, nonadiabatic molecular dynamics and machine learning, we advance quantum dynamics simulation to nanosecond timescale and demonstrate that large fluctuations of MHP defect energy levels extend light absorption to longer wavelengths and enable trapped charges to escape into bands. This allows low energy photons to contribute to photocurrent through energy up-conversion. Deep defect levels can become shallow transiently and vice versa, altering the traditional defect classification into shallow and deep. While defect levels fluctuate more in MHPs than traditional semiconductors, some levels, e.g., Pb interstitials, remain far from band edges, acting as charge recombination centers. Still, many defects deemed detrimental based on static structures, are in fact benign and can contribute to energy up-conversion. The extended light harvesting and energy up-conversion provide strategies for design of novel solar, optoelectronic, and quantum information devices.